2023
DOI: 10.1021/acs.molpharmaceut.3c00095
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Efficient Synthesis of 3-Aryl-2-oxazolidinone Scaffolds Enabling Increased Potency toward Biofilms

Abstract: Infectious diseases caused by bacterial pathogens are a leading cause of mortality worldwide. In particular, recalcitrant bacterial communities known as biofilms are implicated in persistent and difficult to treat infections. With a diminishing antibiotic pipeline, new treatments are urgently required to combat biofilm infections. An emerging strategy to develop new treatments is the hybridization of antibiotics. The benefit of this approach is the extension of the useful lifetime of existing antibiotics. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…In comparison to linezolid, the structure of ranbezolid replaces the morpholine moiety with a piperazine ring attached to a nitrofuran via a methylene linker. Our previous work showed the piperazinyl oxazolidinone derivative is not able to eradicate S. aureus biofilms completely [59]. Therefore, it is suspected that the key to ranbezolid's potent antibiofilm activity lies in its nitrofuran ring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to linezolid, the structure of ranbezolid replaces the morpholine moiety with a piperazine ring attached to a nitrofuran via a methylene linker. Our previous work showed the piperazinyl oxazolidinone derivative is not able to eradicate S. aureus biofilms completely [59]. Therefore, it is suspected that the key to ranbezolid's potent antibiofilm activity lies in its nitrofuran ring.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that ranbezolid functions as a 'dual-warhead' drug to eradicate biofilms and acts via the oxazolidinone mode of action and as either a nitric oxide donor or cytotoxic drug because of its nitrofuran ring (Figure 4). While the exact mechanism of action of nitroxide hybrid drugs is currently unknown [59,60,87], nitroxides are considered to be nitric oxide mimics. Combination treatment was then used to explore whether the susceptibility of ranbezolid and linezolid could be enhanced with the nitroxide C-TEMPO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular docking experimental method: delete Tiamulin and water molecules on 1XBP, hydrogenate and assign Gasteiger charges, prepare receptor molecules and ligand molecules by AutoDockTools, set the box with the initial ligand Tiamulin as the center of the box (center_x = 52.564, center_y = 123.356, center_z = 114.265), box size (20,20,20). AutoDock Vina 36 was employed for molecular docking and the docking results were analyzed using Pymol.…”
Section: -(3-((s)-5-(aminomethyl)-3-(3-bromophenyl)-2oxazolidinone)et...mentioning
confidence: 99%
“…Modification of the pleuromutilin parent ring is difficult, and the antibacterial activity does not improve significantly. , Some studies have suggested that all pleuromutilin derivatives have a similar binding mode in the tricyclic mutilin core when combined with PTC, while the C-14 side chain varies considerably in the binding position. , In particular, the incorporation of five-membered heterocycles, such as triazole and oxadiazole, into the side chain of pleuromutilin enhances its antibacterial performance. Oxazolidinone is a bioactive fragment that has been introduced as an active functional group in the development of antibacterial drugs with good results. For example, linezolid, tedizolid, and contezolid have been successively approved, which has greatly increased our interest in introducing these active structures. Furthermore, oxazolidinone has the advantage of containing multiple heteroatoms, which allows it to bind to surrounding receptor residues and improve water solubility.…”
mentioning
confidence: 99%